ÎNFIINŢAREA SECŢIEI DE GEOGRAFIE ŞI A INSTITUTULUI SĂU DIN CADRUL FACULTĂŢII DE ŞTIINŢE DE LA UNIVERSITATEA DACIEI SUPERIOARE DIN CLUJ - PĂCURAR, Alexandru (Studia Universitatis Babeș-Bolyai Geographia, 2020)
The setting up of the Geography Department and its Institute within the Faculty of Sciences at the Upper Dacia University of Cluj. On 16 August 1919, the University Board, the organ created for the organization and employment of teaching staff for the Upper Dacia University of Cluj after its transition to Romanian administration (12 May 1919), presented and proposed the organisational chart by departments, seminars, laboratories and institutes of the future Faculty of Sciences, by means of the Board rapporteurs, scientists Gheorghe Țițeica, Ludovic Mrazec and Alexandru Borza. At the express request of professor George Vâlsan, the tertiary geographical education was also included in this Faculty, as an independent department, the Department of Geography, consisting of two sections and an Institute of Geography. This was a new situation, different from the study of Geography at the universities in Iași and Bucharest. The organisational chart of Cluj University, made according to the ”German model”, was kept until the Stalinist reform of the Romanian education on 3 August 1948. By means of suggestive examples, the main Romanian university institutions newly-created at Cluj University are illustrated and described, some of them under the auspices of the Royal Foundations, such as the Astronomic Observatory and the Institute of Chemistry and Physics, as well as others, like the Sports Park, the new Botanical Garden with the Botanic Museum, the Palace of University Clinics, the Academic College and the Ethnographic Park and Museum. The materialization of George Vâlsan’s concept regarding the study of Geography and its relations to the other departments of Cluj University, as well as the their scientific and logical foundation within the double specialization, are extensively presented, as a proof of the scientist’s determination to lay solid grounds to the Romanian tertiary geographical education at Cluj University. RÉSUMÉ. Création du Département de géographie et de son institut au sein de la Faculté des sciences de l’Université de la Dacie supérieure à Cluj. La commission universitaire, organisme créé dans le but d’employer et d’organiser le personnel enseignant de l’Université de la Dacie supérieure à Cluj après son transfert à l’administration roumaine (le 12 mai 1919), a présenté et proposé le 16 août 1919 l’organigramme de la future Faculté des sciences, structuré par départements, séminaires, laboratoires et instituts. Les rapporteurs de la commission étaient les scientifiques Gheorghe Țițeica, Ludovic Mrazec et Alexandru Borza. À la demande expresse du professeur George Vâlsan, cette faculté comprenait une section autonome consacrée à l’enseignement supérieur de la géographie – la section de géographie – composée de deux chaires et d’un Institut de géographie, ce qui représentait une nouveauté par rapport à l’étude de la géographie aux universités de Jassy et de Bucarest. L’organigramme de l’Université de Cluj, réalisé d’après le «modèle allemand», a été conservé jusqu’à la réforme stalinienne de l’enseignement roumain, le 3 août 1948. Dans la présente contribution, nous illustrons et décrivons par des exemples suggestifs les principales institutions universitaires roumaines nouvellement créées à l’Université de Cluj, certaines d’entre elles sous les auspices des Fondations royales (les cas de l’Observatoire astronomique et de l’Institut de chimie et de physique), mais non seulement (le Parc des sports, le nouveau Jardin botanique avec son Musée botanique, le Collège académique ou le Parc et le Musée ethnographiques). Nous présentons dans le détail la mise en œuvre de la conception de George Vâlsan sur l’enseignement de la géographie et ses rapports avec les autres chaires de l’Université de Cluj, ainsi que leur justification scientifique et logique dans le cadre de la double spécialisation, afin de prouver la détermination de ce scientifique à jeter des bases solides pour l’enseignement supérieur roumain de la géographie à l’Université de Cluj. Mots clés : Université de la Dacie Supérieure de Cluj, Département de Géographie, Faculté des Sciences.